Alkaloids extract of Alnus nepalensis bark as a green inhibitor for mild steel corrosion in 1 M H2SO4 solution - Dhakal, Kamala; Bohora, Dilip; Bista, Birendra; Oli, Hari; Singh, Sanjay; Bhattarai, Deval; Karki, Nabin; Yadav, Amar (Journal of Nepal Chemical Society, 2022)
Extraction of alkaloids from Alnus nepalensis bark has been successfully carried out and used as a green inhibitor for mild steel corrosion exposed to 1 M H2SO4 solution. Alkaloids have been tested by chemical, UV and FTIR spectroscopic methods.Corrosion inhibition was monitored by weight loss measurement and electrochemical methods(open circuit potential method and potentiodynamic polarization method). Weight loss measurement was employed to study the inhibitor concentration and immersion time effect. Similarly, the temperature effect on inhibition efficiency was also carried out by this method. The maximum corrosion inhibition efficiency observed for 1000 ppm solution for 3 h was 71.94 % at 25 °C. The OCP measurement revealed that alkaloids acted as a mixed type of inhibitor. Potentiodynamic polarization for 3 h immersed samples in the presence and absence of inhibitors was carried out. The corrosion current density was decreased with the increasing concentration. The maximum efficiency of immersed sample in 1000 ppm inhibitor solution was 78.48 %. The adsorption isotherm and thermodynamic parameters were calculated and the energy of activation (Ea) was found to be 71.41 kJ/mol. The positive value of enthalpy indicated that the reaction involves is endothermic.